The Effect of Kegel Exercises Program on Sexual Function of Patients Diagnosed with Chronic Prostatitis - Atef Gomaa Ramadan; Afaf Salah Abd El-mohsen; Hala Hassan Sayed; Afaf Mayada Taha Mahmoud (GLOBAL HEALTH SCIENCE GROUP, 2022)
Chronic prostatitis is a common urological diagnosis in men of all ages in Egypt. chronic prostatitis causes many men significant morbidity and the main four symptom domains of chronic prostatitis are urogenital pain, lower urinary tract symptoms, psychological issues and sexual dysfunction.The aim of the study: To study the effect of Kegel exercises on patients diagnosed with chronic prostatitis. A purposive sample was used for this study, 94 patients with chronic prostatitis. This study was conducted at the urology outpatient clinics at El-Fayoum University and General Hospitals at El-Fayoum City. Data were collected utilizing the following four tools: Tool (1): An interview questionnaire, it consists of four parts: Part I: Socio-demographic data of the clients. Part II: Past and present medical, surgical history. Part III: knowledge of patients regarding Kegel exercises. Part IV: patient's practices regarding Kegel exercises. Tool II - Sexual Health Inventory for Men. The present study revealed that slightly less than half of the studied samples were in age group of 41-55 years with mean age 56.28±12.29. Additionally, it was found that there is a highly statistically significant between total practices scores in pre ,post and follow up test and the majority of the studied samples had an satisfactory practice in post test as well as the study showed that that there was a highly statistically significant of total practice with level of education and Social status. Based on the findings and research hypothesis, of the study it was concluded that the implementation of Kegel exercises program led to improvement in both knowledge and practices regarding chronic prostatitis and Kegel exercises. The improvement in knowledge is essential to improve practice.